Pembinaan Pendidikan Islam Pada Masa Rasulullah Saw - Suriadi, Suriadi (BELAJEA: Jurnal Pendidikan Islam, 2017)
This article discusses the transformation of Islamic education in the early period, that is from the epoch of the prophet Muhammad. In the period of the prophet Muhammad, Islamic education activity took place in its simple form, centered on the companions residents. Prophet Muhammad as uswatun hasanah and rahmatan lil alamin for those expecting the grace and the coming of the Day of Judgment is the first and foremost educators in the world of Islamic education. The transformation process of science, spiritualism internalization of values and emotional guidance of the Prophet Muhammad is incredible miracles and ordinary man may not be able to do so. Implementation of guidance of Islamic education in the time of Prophet Muhammad conducted in two phases which of Mecca, as the initial phase of guidance of Islamic education and the phase of Medina, as the improvement phase guidance of Islamic education.